Intrafamily Resource Allocations: A Dynamic Structural Model of Birth Weight - Del Bono, Emilia; Ermisch, John; Francesconi, Marco (Journal of Labor Economics, 2012)
Using large American and British survey data, this paper provides structural estimates of the production functions for birth weight and fetal growth. In addition to maternal smoking, we estimate the impact of when a mother stops work, which has not been considered in the literature. Mothers’ work interruptions of up to 3 months before birth have a positive effect on birth outcomes, especially among British children. Parental behavior appears to respond to child idiosyncratic endowments in a way that suggests that parents have inequity aversion concerns. Evidence in favor of inequity aversion emerges also from the analysis of breast-feeding decisions.